2018
DOI: 10.1186/s11658-018-0094-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MicroRNA-488 inhibits tongue squamous carcinoma cell invasion and EMT by directly targeting ATF3

Abstract: BackgroundIt has been reported that the expression of activating transcription factor 3 (ATF3) is closely associated with both microRNA (miRNA) processing and the progress of many cancers. Our study aimed to explore the interaction between ATF3 and miR-488 in tongue squamous cell carcinoma (TSCC).MethodsQuantitative real-time PCR was performed to detect the levels of ATF3 and miR-488 in TSCC tissues and cell lines. Cell invasion and epithelial–mesenchymal transition (EMT) were assessed to determine the biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
1
29
1
Order By: Relevance
“…As a novel miRNA, the research focused on miR-488 was limited and reported the downregulation of miR-488 in several human cancers and its low expression significantly correlated with progression, metastasis, and poor survival [5][6][7][8][9] , indicating the tumor-suppressive role of miR-488 in different types of cancers. However, the function and mechanism of miR-488 in breast cancer is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a novel miRNA, the research focused on miR-488 was limited and reported the downregulation of miR-488 in several human cancers and its low expression significantly correlated with progression, metastasis, and poor survival [5][6][7][8][9] , indicating the tumor-suppressive role of miR-488 in different types of cancers. However, the function and mechanism of miR-488 in breast cancer is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation and invasion abilities of hepatocellular carcinoma cells were also inhibited by the high-level of miR-488 through the downregulation of ADAM9 and lncRNA HULC 6 . In tongue squamous carcinoma, miR-488 could increase the sensitivity of tumor cells to chemotherapy 7 , supposed that miR-488 was involved in the inhibition of the epithelial–mesenchymal transition (EMT) process 8 . Recently, Takaaki et al demonstrated that circulating pre-miRNA-488 in peripheral blood would be a potential biomarker for predicting recurrence of breast cancer 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Zhang et al also reports that urothelial cancer associated 1 knockdown significantly suppresses TGFβ1-induced TC cell invasion and EMT by decreasing vimentin and increasing E-cadherin (Zhang et al, 2019). Shi et al discovers that the EMT of TSCC cells is inhibited by ameliorating the expressions of MMP-2 and MMP-9 (Shi et al, 2018). All these data support our point.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that miR-488 is significantly decreased in TSCC tissues and cell lines. Further, knockdown of miR-488 promotes invasion (Shi et al, 2018). Hsa-miR-485-5p reverses epithelial to mesenchymal transition (EMT) and promotes cisplatin-induced cell death by targeting PAK1 in TSCC (Lin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This interaction results in translational suppression and/or mRNA degradation. miRNAs are capable of oncogenic or tumor-suppressive actions in TScc by modulating the processes associated with TScc initiation and progression, such as cell proliferation, cell cycle, apoptosis, angiogenesis Long non-coding RNA PRNCR1 exerts oncogenic effects in tongue squamous cell carcinoma in vitro and in vivo by sponging microRNA-944 and thereby increasing HOXB5 expression and metastasis (21)(22)(23). Therefore, further investigation into the functions of specific lncRNAs and miRNAs in TSCC may highlight promising targets for treating TScc.…”
Section: Introductionmentioning
confidence: 99%